2014
DOI: 10.1186/1471-2407-14-551
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological modulation of autophagy enhances Newcastle disease virus-mediated oncolysis in drug-resistant lung cancer cells

Abstract: BackgroundOncolytic viruses represent a promising therapy against cancers with acquired drug resistance. However, low efficacy limits its clinical application. The objective of this study is to investigate whether pharmacologically modulating autophagy could enhance oncolytic Newcastle disease virus (NDV) strain NDV/FMW virotherapy of drug-resistant lung cancer cells.MethodsThe effect of NDV/FMW infection on autophagy machinery in A549 lung cancer cell lines resistant to cisplatin (A549/DDP) or paclitaxel (A54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 56 publications
1
44
1
1
Order By: Relevance
“…The increased HVJ-E-mediated apoptosis in the presence of autophagy modulators was further verified by enhanced caspase-3 and PARP cleavage. Interestingly, Jiang et al recently reported that neither CQ nor rapamycin could augment the anticancer effects of NDV in A549 cells, which differs from the current results [3]. Therefore, it is possible that the decision whether to use autophagy inducers or inhibitors in combination virotherapy should be virus strain-and cancer cell line-dependent.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…The increased HVJ-E-mediated apoptosis in the presence of autophagy modulators was further verified by enhanced caspase-3 and PARP cleavage. Interestingly, Jiang et al recently reported that neither CQ nor rapamycin could augment the anticancer effects of NDV in A549 cells, which differs from the current results [3]. Therefore, it is possible that the decision whether to use autophagy inducers or inhibitors in combination virotherapy should be virus strain-and cancer cell line-dependent.…”
Section: Discussioncontrasting
confidence: 51%
“…This effect was caused by inhibition of the class I PI3K/Akt/ mTOR/p70S6K pathway, which negatively regulates autophagy [22]. Previous studies reported that cisplatin treatment induces autophagy in A549 cells, and the acquired cisplatin resistance in A549 cells is associated with enhanced autophagy, suggesting that autophagy may act as a survival mechanism in cisplatin-resistant A549 lung cancer cells [3,23]. Having documented that HVJ-E induces both apoptosis and autophagy in A549 and A549/DDP cells, we next investigated the role that autophagy plays in apoptosis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is therefore possible that perifosine and MK-2206, the AKT inhibitors already being used for gliomas, could be combined with 2-DG to produce a synergistic effect and to reverse the effect of autophagy to apoptosis. In a recent study by Jiang et al [33], it was shown that autophagic modulators like rapamycin and CQ can enhance the in vitro and in vivo oncolytic effects of Newcastle disease virus-mediated oncolysis in drug-resistant lung cancer cell lines. Autophagic inhibitors along with the conventional chemotherapy can thus prove to be rational combinations for reducing chemoresistance in different cancers.…”
Section: Discussionmentioning
confidence: 98%
“…Keeping this in mind, our next aim characterizing rNDV-P05 was to explore whether the virus had the capability or not to induce apoptosis over a panel of tumor cell lines from a variety of tissues. In this study, we have demonstrated that rNDV-P05 was able to induce apoptosis over four from five tested cell lines, which had previously shown susceptibility to NDV (29)(30)(31)(32). In solid tumors, this is important for virotherapy, given that the cell death induced by the virus in the tumor microenvironment can evoke not only local, but also a systemic tumor-specific immune surveillance against primary and metastatic malignant cells.…”
Section: Discussionmentioning
confidence: 99%